Between Normativism and Phenomenology: on the Influence of Adolf Reinach’s Concept of Social Acts on Szymon Rundstein’s Theory of Law - Tkacz, Sławomir; Wentkowska, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This text is devoted to commemorating Professor Tomasz Bekrycht, who was an eminent expert in the phenomenology of law. His interests focused particularly on the analysis of the philosophical and legal views of Adolf Reinach. The undoubted achievement of Professor Tomasz Bekrycht is that he restored the works of Adolf Reinach to Polish theory and philosophy of law. This study focuses on the references to A. Reinach’s concept of social acts in the indicated work by Szymon Rundstein, who does not ignore the concept of social acts in his considerations, but treats it as an interesting theoretical and legal suggestion. While analysing the influence of phenomenological concepts on Rundstein’s theory, an important conclusion was made: as a normativist, Rundstein accepts the concept of the “basic norm” (Grundnorm), suggested by Hans Kelsen, which legitimises law (the validity of other legal norms within the system).